Erratum to: Search for PeVatrons at the Galactic Center using a radio air-shower array at the South Pole - A. Balagopal V.; A. Haungs; T. Huege; F. G. Schröder (The European Physical Journal C, 2021)
A Correction to this paper has been published: https://doi.org/10.1140/epjc/s10052-018-5537-2